HADITS AL-WALAD LI AL-FIRASY SEBAGAI PENETAPAN NASAB ANAK - Asriaty, Asriaty (DIKTUM: Jurnal Syariah dan Hukum, 2010)
Islam is highly concerned with children, even though they are born from marriage by accident, or their existence are not recognized by their motherâs legal husband. One of the bases to determine the genealogy of a child is the hadits which runs, âal-walad li al-firasy, wa li al-akhir al-hajar.â This hadits explains that a childâs genealogy is associated with his/her motherâs legal husband; if there is a man claims that the child is his son/daughter, his claim is rejected. This aims at maintaining the cohesion of the legal family and, especially, for the atvantage of the child. The sentence al-walad li al-firasy in the hadits is gharib in pattern. In commentary books, many Islamic scholars try to give comprehensive explanation on this issue. The point that makes the Islamic scholars different in interpreting the hadits is the application of the word firasy for slaves and the order of hijab by our prophet to Sawdah binti Zamâah. In this modern era, when free-sex life style prevails, the presence of a child from marriage by accident should have a solution. It will be an ironic situation if a child has to pay all the risks of the bad deed of his/her parent. Therefore, the interpretation towards the sentence al-walad li al-firasy in the hadits should by comprehensive, so that Islamic law will give positive contribution in overcoming contemporary problems of Muslimsâ life in general, and the life of young Muslim generation in particular.